Preparation method of silicon dioxide aerogel microspheres

A method using calcination and alkali dissolution of fly ash acid slag to produce silica aerogel microspheres addresses the inefficiencies of existing processes, achieving cost-effective and environmentally friendly large-scale production of silica aerogel microspheres with enhanced hydrophobicity.

CN119240717APending Publication Date: 2025-01-03CHINA SHENHUA ENERGY CO LTD HARWUSU OPEN-PIT COAL MINE +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411363520.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing methods for preparing silicon-based aerogels using fly ash acid slag as a raw material are costly and complex, and there is a need for a more efficient and environmentally friendly process.

Method used

A method involving calcination, alkali dissolution, and solid-liquid separation of fly ash acid slag to produce a sodium silicate solution, followed by hydrolysis and surface modification with organosiloxane compounds to create silica aerogel microspheres, enhancing hydrophobicity and reducing costs.

Benefits of technology

The method efficiently utilizes fly ash acid slag to produce silica aerogel microspheres with excellent hydrophobicity, reducing costs and environmental impact while being suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065510500000171
    Figure BDA0005065510500000171
  • Figure BDA0005065510500000181
    Figure BDA0005065510500000181
Patent Text Reader

Abstract

The invention provides a preparation method of silicon dioxide aerogel microspheres. The silicon dioxide aerogel microspheres with excellent hydrophobicity are prepared by taking fly ash acid-soluble slag as a raw material. The method comprises the following steps: treating fly ash acid-soluble slag to obtain a sodium silicate solution; treating the sodium silicate solution to obtain silicon dioxide alcosol; respectively adding the silicon dioxide alcosol and ammonia water into an oil phase to form silicon dioxide wet gel microspheres; the preparation method comprises the following steps: carrying out surface modification on silicon dioxide wet gel microspheres by adopting an organosiloxane compound, and then washing and drying to prepare the silicon dioxide aerogel spheres. Wherein the organosiloxane compound comprises at least one of vinyl trimethoxy silane and vinyl tri (beta-methoxyethoxy) silane, and the organic siloxane compound comprises at least one of vinyl trimethoxy silane and vinyl tri (beta-methoxyethoxy) silane. The organosiloxane compound is hydrolyzed to generate silanol groups, the silanol groups are chemically combined with SiO2, moisture on the surface of SiO2 can be removed, hydrophobic groups can be connected to the surface of SiO2, and therefore the hydrophobicity of the silicon dioxide aerogel microspheres is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of comprehensive utilization of industrial solid waste, and in particular to a method for preparing silicon dioxide aerogel microspheres. Background Art

[0002] Aerogel is a porous network structure composed of nanoparticles, with a porosity of up to 85% to 95%, and a solid material filled with a gaseous dispersion medium in its network. Due to its unique structure, aerogel has the characteristics of high specific surface area, low density, and low thermal conductivity, and has a wide range of applications in thermal, acoustic, and catalytic science. As a branch of the aerogel field, SiO2 aerogel microspheres have high load capacity, excellent adsorption performance, and good biocompatibility. They have very broad application prospects in many fields and are a promising nanoporous material that has attracted widespread attention. At present, research on SiO2 aerogel microspheres has been reported, but there are still some shortcomings in the preparation method. Most of them use tetraethyl orthosilicate as raw material and are prepared by supercritical drying, which leads to high cost and complicated preparation process. In addition, there are also problems such as complex oil phase composition.

[0003] Fly ash is a waste discharged from coal-fired power plants. Because it contains rich chemical elements such as aluminum, silicon, iron, calcium, and magnesium, it is often used as a "secondary resource". Among them, the most widely used application research is to extract alumina from fly ash. The methods for extracting aluminum from fly ash mainly include acid method, alkali method, and acid-base combined method. If the residue after aluminum extraction from fly ash is not utilized, it will still cause environmental pollution. After aluminum is extracted from fly ash by acid method or acid-base combined method, SiO2 is enriched in the tailings. If the tailings after aluminum extraction from fly ash (fly ash acid slag) are used as a silicon source to prepare silicon-based aerogels, high-value utilization of industrial solid waste can be achieved, which can not only reduce the raw material cost of silicon-based products, but also avoid secondary pollution of aluminum extraction residues. However, how to prepare silicon-based aerogels using fly ash acid slag after aluminum extraction from fly ash as raw material is a problem that technicians in this field need to solve urgently. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing silica aerogel microspheres, so as to solve the problem of how to prepare silicon-based aerogel using fly ash acid-soluble slag after aluminum extraction from fly ash as raw material in the prior art.

[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing silica aerogel microspheres is provided, comprising the following steps: step S1, calcining, alkali dissolving and solid-liquid separation of fly ash acid slag in sequence to obtain a sodium silicate solution; step S2, mixing the sodium silicate solution, alcohol and optional water to obtain a sodium silicate alcohol solution, and hydrolyzing the sodium silicate alcohol solution to obtain a silica alcohol sol; step S3, respectively introducing the silica alcohol sol and ammonia water into an oil phase until the pH of the obtained oil phase mixed solution is 7-8, and performing solid-liquid separation to obtain a silica wet gel microsphere; step S4, surface-modifying the silica wet gel microspheres with an organic siloxane compound to obtain a surface-modified gel microsphere; wherein the organic siloxane compound comprises at least one of vinyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane; step S5, washing and drying the surface-modified gel microspheres to obtain silica aerogel microspheres.

[0006] Furthermore, in step S1, the fly ash acid slag mainly includes SiO2 and Al2O3, wherein the mass fraction of SiO2 is 60-70wt%, and the mass fraction of Al2O3 is 10-25wt%.

[0007] Furthermore, in step S1, the calcination temperature is 600-850° C., and the calcination time is 1-2 hours.

[0008] Furthermore, in step S1, an alkaline solution is used for alkaline dissolution treatment, and the alkaline solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, and a sodium carbonate solution.

[0009] Furthermore, the concentration of the alkaline solution is 4 to 6 mol / L.

[0010] Furthermore, the mass ratio of fly ash acid slag to alkaline solution is 1:5 to 1:9.

[0011] Furthermore, the temperature of the alkali dissolution treatment is 60 to 100° C.; and the time of the alkali dissolution treatment is 2.5 to 5 hours.

[0012] Furthermore, in step S2, the mass ratio of the sodium silicate solution, alcohol and optional water is 1:(5-10):(2-5).

[0013] Furthermore, the alcohol includes at least one of isopropanol and ethylene glycol.

[0014] Furthermore, the temperature of the hydrolysis treatment is 40 to 80° C., and the time of the hydrolysis treatment is 6 to 24 hours.

[0015] Furthermore, in step S2, an acid solution is used to adjust the pH of the sodium silicate alcohol solution to 1-3 and then the solution is hydrolyzed.

[0016] Furthermore, the acid solution includes at least one of an inorganic acid solution and an organic acid solution.

[0017] Furthermore, the inorganic acid solution includes at least one of a hydrochloric acid solution and a nitric acid solution.

[0018] Furthermore, the organic acid solution is a glycolic acid solution.

[0019] Furthermore, the concentration of the inorganic acid solution is 4 to 6 mol / L.

[0020] Further, in step S3, the oil phase includes mineral oil, alkane and emulsifier; wherein, based on the total volume of the oil phase being 100%, the volume proportion of the emulsifier is 2-8%, and the volume ratio of the mineral oil to the alkane is (1-1.5):1;

[0021] Further, the mineral oil includes at least one of paraffin oil, diesel oil, and kerosene;

[0022] Further, the alkane includes at least one of n-heptane, n-hexane, and n-octane;

[0023] Furthermore, the emulsifier includes at least one of OP-7 and TX-7.

[0024] Furthermore, in step S3, the flow ratio of the silica alcohol sol to the ammonia water is 1:3 to 1:6; furthermore, the mass fraction of the ammonia water is 25 to 28%.

[0025] Furthermore, the surface modification temperature is 30 to 60° C., and the surface modification time is 6 to 18 hours.

[0026] Furthermore, in step S5, washing is performed using a washing solution, and the washing solution includes at least one of methanol and anhydrous ethanol.

[0027] Furthermore, the washing time is 0.25 to 0.5 h.

[0028] Furthermore, the drying temperature is 50 to 80° C., and the drying time is 8 to 16 hours.

[0029] By applying the technical scheme of the present invention, the present application uses fly ash acid slag to prepare silica aerogel microspheres with excellent hydrophobicity. The fly ash acid slag is calcined and alkali-dissolved in sequence to dissolve SiO2 in the fly ash acid slag, and a sodium silicate solution is obtained by solid-liquid separation. The sodium silicate solution, alcohol and optional water are then mixed and hydrolyzed to obtain a silica alcohol sol. The silica alcohol sol and ammonia water are respectively introduced into the oil phase. Due to the effect of surface tension, the silica alcohol sol is sol-gelled in the oil phase to form silica wet gel microspheres and evenly dispersed in the oil phase. The introduction of ammonia water increases the pH of the oil phase mixed solution, thereby causing the silica gel microspheres to precipitate, and the silica wet gel microspheres are obtained after solid-liquid separation. The surface of the wet silica gel microspheres is modified by using a specific organosiloxane compound, which can hydrolyze in water (including free water adsorbed on the surface of the silica gel) to produce silanol groups, which are chemically combined with SiO2 or with the original silane alcohol groups on the surface, which can not only remove moisture from the surface of SiO2, but also connect hydrophobic groups to the surface of SiO2, thereby improving the hydrophobicity of the silica gel microspheres. Then, the silica aerogel spheres with excellent hydrophobicity are prepared by washing and drying.

[0030] In addition, the preparation method provided in the present application not only efficiently utilizes fly ash acid slag and reduces costs, but also the preparation method is simple, easy to operate, and suitable for large-scale production. DETAILED DESCRIPTION

[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0032] As analyzed in the background technology of this application, there is a problem in the prior art on how to prepare silicon-based aerogel using fly ash acid-soluble slag after aluminum extraction from fly ash as raw material. In order to solve this problem, this application provides a method for preparing silica aerogel microspheres.

[0033] In a typical embodiment of the present application, a method for preparing silica aerogel microspheres is provided, comprising the following steps: step S1, calcining, alkali dissolving, and solid-liquid separation of fly ash acid slag in sequence to obtain a sodium silicate solution; step S2, mixing the sodium silicate solution, alcohol, and optional water to obtain a sodium silicate alcohol solution, and hydrolyzing the sodium silicate alcohol solution to obtain a silica alcohol sol; step S3, respectively introducing the silica alcohol sol and ammonia water into an oil phase until the pH of the obtained oil phase mixed solution is 7 to 8, and performing solid-liquid separation to obtain silica wet gel microspheres; step S4, surface-modifying the silica wet gel microspheres with an organic siloxane compound to obtain surface-modified gel microspheres; wherein the organic siloxane compound includes at least one of vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane; step S5, washing and drying the surface-modified gel microspheres to obtain silica aerogel microspheres.

[0034] The present application uses fly ash acid slag to prepare silica aerogel microspheres with excellent hydrophobicity. The fly ash acid slag is calcined and alkali-dissolved in sequence to dissolve SiO2 in the fly ash acid slag, and a sodium silicate solution is obtained through solid-liquid separation. The sodium silicate solution, alcohol and optional water are then mixed and hydrolyzed to obtain a silica alcohol sol. The silica alcohol sol and ammonia water are respectively introduced into the oil phase. Due to the effect of surface tension, the silica alcohol sol undergoes sol-gel in the oil phase to form silica wet gel microspheres and are uniformly dispersed in the oil phase. The introduction of ammonia water increases the pH of the oil phase mixed solution, thereby causing the precipitation of the silica wet gel microspheres, and the silica wet gel microspheres are obtained after solid-liquid separation. The surface of the wet silica gel microspheres is modified by using specific organosiloxane compounds. The organosiloxane compounds can be hydrolyzed in water (including free water adsorbed on the surface of the silica gel microspheres) to produce silanol groups, which are chemically combined with SiO2 or with the original silane alcohol groups on the surface, which can not only remove moisture from the SiO2 surface, but also connect hydrophobic groups to the SiO2 surface, thereby improving the hydrophobicity of the silica gel microspheres. Then, the silica aerogel spheres with excellent hydrophobicity are prepared by washing and drying.

[0035] In addition, the preparation method provided in the present application not only efficiently utilizes fly ash acid slag and reduces costs, but also the preparation method is simple, easy to operate, and suitable for large-scale production.

[0036] In some embodiments, the fly ash acid slag mainly includes SiO2 and Al2O3, wherein the mass fraction of SiO2 is 60-70wt%, and the mass fraction of Al2O3 is 10-25wt%. In addition to SiO2 and Al2O3, the fly ash acid slag also includes one or more metal oxides such as TiO2, CaO, MgO, Fe2O3, K2O, and Na2O. Preferably, the fly ash acid slag is the tailings after alumina is extracted from fly ash in the Jungar mining area of ​​Inner Mongolia by a "one-step acid dissolution method".

[0037] In the present application, the fly ash acid slag obtained after extraction of alumina from fly ash can have the mass fraction of each component appropriately adjusted according to actual production, and the mass fraction of each component in the fly ash acid slag can be within the above range.

[0038] Typically but not limitatively, the mass fraction of SiO2 in the fly ash acid slag is 60wt%, 62wt%, 64wt%, 66wt%, 68wt%, 70wt% or a range consisting of any two values; the mass fraction of Al2O3 in the fly ash acid slag is 10wt%, 13wt%, 16wt%, 19wt%, 22wt%, 25wt% or a range consisting of any two values.

[0039] The main component of the tailings obtained from fly ash through the acid method and the acid-base combined method is SiO2, and after aluminum extraction, SiO2 is enriched in the tailings. The fly ash acid-soluble slag after the extraction of alumina is fully utilized to prepare it into silica aerogel microspheres, realizing the resource utilization of fly ash aluminum extraction tailings, protecting the ecological environment, and reducing the preparation cost of silica aerogel microspheres.

[0040] In order to further improve the removal rate of impurities during the calcination process and further improve the purity of the sodium silicate solution, the calcination temperature is preferably 600-850° C. and the calcination time is 1-2 hours.

[0041] Typically but not limiting, the calcination temperature is 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or a range consisting of any two values; the calcination time is 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h or a range consisting of any two values.

[0042] In addition to SiO2, fly ash acid slag also contains other metal oxides, among which Al2O3 accounts for a large proportion. Alkaline dissolution treatment is performed on fly ash acid slag to dissolve SiO2 from fly ash acid slag, which can not only efficiently extract SiO2 from fly ash acid slag, but also reduce the extraction of Al2O3 or other metal oxides and affect the purity of the product. SiO2 is dissolved in alkaline solution, and solid-liquid separation is performed to obtain sodium silicate solution and desiliconized slag.

[0043] The method of obtaining the sodium silicate solution by solid-liquid separation in the present application is not specifically limited, and any solid-liquid separation method commonly used in the art can be used. For ease of operation, it is preferred to obtain the sodium silicate solution by filtration.

[0044] In some embodiments, an alkaline solution is used for alkaline dissolution treatment, and the alkaline solution preferably includes any one or more of a sodium hydroxide solution, a potassium hydroxide solution, and a sodium carbonate solution; further preferably, the concentration of the alkaline solution is 4 to 6 mol / L, and the mass ratio of the fly ash acid slag to the alkaline solution is 1:5 to 1:9.

[0045] In the alkali dissolution treatment, an alkali solution is used to react with silicon dioxide, so that silicon dioxide enters the solution to generate a sodium silicate solution, thereby achieving the dissolution of silicon dioxide from the fly ash acid slag. The dissolution rate of silicon dioxide in the fly ash acid slag is further increased by using any one or more of a sodium hydroxide solution, a potassium hydroxide solution, and a sodium carbonate solution for alkali dissolution treatment, or by adjusting the concentration of the alkali solution and the solid-liquid ratio of the fly ash acid slag to the alkali solution within the above range.

[0046] Typically but not limiting, the concentration of the alkaline solution is 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6 mol / L or a range consisting of any two values; the mass ratio of fly ash acid slag to alkaline solution is 1:5, 1:6, 1:7, 1:8, 1:9 or a range consisting of any two values.

[0047] In order to further promote the dissolution of silicon dioxide, the temperature of the alkali dissolution treatment is preferably 60 to 100° C. and the time of the alkali dissolution treatment is 2.5 to 5 hours.

[0048] Typically but not limiting, the temperature of the alkali dissolution treatment is 60°C, 70°C, 80°C, 90°C, 100°C or a range consisting of any two values; the time of the alkali dissolution treatment is 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range consisting of any two values.

[0049] In order to further obtain a sodium silicate alcohol solution and create favorable conditions for the subsequent silica alcohol sol, the mass ratio of the sodium silicate solution, alcohol and optional water is preferably 1:(5-10):(2-5); further preferably, the alcohol comprises any one or more of isopropanol and ethylene glycol.

[0050] Typically but not limiting, the mass ratio of sodium silicate solution, alcohol and optional water is, for example, 1:8:2, 1:7:2, 1:7:3, 1:5:5, 1:10:4 or a range consisting of any two of these values.

[0051] In order to further increase the reaction rate of hydrolysis and the generation rate of silica alcohol sol, it is preferred that the hydrolysis treatment temperature is 40 to 80° C. and the hydrolysis treatment time is 6 to 24 h.

[0052] Typically but not limiting, the temperature of the hydrolysis treatment is 40°C, 50°C, 60°C, 70°C, 80°C or a range consisting of any two values; the time of the hydrolysis treatment is 6h, 10h, 14h, 18h, 20h, 24h or a range consisting of any two values.

[0053] In some embodiments, in step S2, an acid solution is used to adjust the pH of the sodium silicate alcohol solution to 1-3 before the hydrolysis treatment is performed, and the acid solution provides an acidic environment for the hydrolysis to further promote the formation of the silica alcohol sol.

[0054] In order to further promote the formation of silica alcohol sol, the acid solution preferably includes any one or more of an inorganic acid solution and an organic acid solution; it is further preferred that the inorganic acid solution includes any one or more of a hydrochloric acid solution and a nitric acid solution, and it is further preferred that the concentration of the inorganic acid solution is 4 to 6 mol / L; the organic acid solution is preferably an ethanolic acid solution, and it is further preferred that the mass fraction of the ethanolic acid solution is 70 wt%.

[0055] Typically but not limiting, before the hydrolysis treatment, the pH of the sodium silicate alcohol solution is adjusted to 1, 1.5, 2, 2.5, 3 or a range consisting of any two values; the concentration of the inorganic acid solution is 4mol / L, 4.5mol / L, 5mol / L, 5.5mol / L, 6mol / L or a range consisting of any two values.

[0056] The silica alcohol sol is added to the oil phase formed by mineral oil, alkane and emulsifier. Due to the effect of surface tension, the silica alcohol sol undergoes sol-gel in the oil phase to form silica wet gel microspheres and are uniformly dispersed in the oil phase. The addition of ammonia water increases the pH of the oil phase mixed liquid, thereby precipitating the silica wet gel microspheres dispersed in the oil phase. The silica wet gel microspheres are obtained through solid-liquid separation.

[0057] When the emulsifier content in the oil phase is too high, not only will the obtained silica wet gel microspheres show obvious agglomeration, but also will cause demulsification and make the washing process more difficult, and the oil phase will be more difficult to remove. When the emulsifier content in the oil phase is too low, the amount of emulsifier adsorbed on the surface of each droplet will be relatively small, and the strength of the formed interfacial film will be low, which will not only easily cause small droplets to collide and condense into large droplets during stirring, but also reduce the stability of the emulsion, and the microspheres will easily break during stirring.

[0058] In order to further avoid agglomeration of the wet silica gel microspheres and maintain the stability of the oil phase to avoid fragmentation of the wet silica gel microspheres, it is preferred that the volume of the emulsifier is 2-8% based on the total volume of the oil phase as 100%, and the volume ratio of mineral oil to alkane is (1-1.5):1.

[0059] Typically but not limiting, the volume ratio of mineral oil to alkane is, for example, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1 or a range consisting of any two values; based on the total volume of the oil phase as 100%, the volume of the emulsifier is, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8% or a range consisting of any two values.

[0060] In order to further promote the uniform dispersion of the silica alcohol sol in the oil phase to form silica wet gel microspheres, the preferred mineral oil includes any one or more of paraffin oil, diesel, and kerosene, the preferred alkane includes any one or more of n-heptane, n-hexane, and n-octane, and the preferred emulsifier includes any one or more of OP-7 and TX-7.

[0061] In order to further increase the uniformity of the wet silica gel microspheres, the flow ratio of the silica alcohol sol to the ammonia water is preferably 1:3 to 1:6; more preferably, the mass fraction of the ammonia water is 25 to 28%.

[0062] Typically but not limiting, the flow rate of silica alcohol sol to ammonia water is, for example, 1:3, 1:4, 1:5, 1:6 or a range consisting of any two values.

[0063] The method of obtaining wet silica gel microspheres by solid-liquid separation is not particularly limited, and any solid-liquid separation method commonly used in the art can be used. For ease of operation, the preferred method of obtaining wet silica gel microspheres by solid-liquid separation is centrifugation.

[0064] While using organosiloxane compounds to modify the surface of silica wet gel microspheres, they can also play an aging role, enhance the stability and strength of the silica aerogel microspheres, avoid shrinkage and cracking of the silica aerogel microspheres during the subsequent drying process, and also make the silica aerogel microspheres smaller in particle size and more evenly distributed.

[0065] In order to further improve the performance of silica aerogel microspheres, the surface modification temperature is preferably 30-60° C. and the surface modification time is 6-18 h.

[0066] Typically but not limiting, the temperature of surface modification is 30°C, 35°C, 40°C, 45°C, 50°C, 60°C or a range consisting of any two values; the time of surface modification is 6h, 9h, 12h, 15h, 18h or a range consisting of any two values.

[0067] In some embodiments, washing is performed with a washing solution, preferably the washing solution includes any one or more of methanol and anhydrous ethanol, and the washing time is preferably 0.25-0.5 h to remove the residual oil phase on the surface modified gel microspheres, and further avoid the influence of impurities on the properties of the silica aerogel microspheres.

[0068] In order to further promote the formation of silica aerogel microspheres, the drying temperature is preferably 50 to 80° C. and the drying time is 8 to 16 hours.

[0069] Typically but not limiting, the drying temperature is 50°C, 60°C, 70°C, 80°C or a range consisting of any two values; the drying time is 8h, 10h, 11h, 12h, 13h, 14h, 15h, 16h or a range consisting of any two values.

[0070] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0071] The components and mass fractions of the fly ash acid slag provided in the examples and comparative examples of the present application are shown in Table 1 (unit: wt %).

[0072] Table 1

[0073] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> CaO MgO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> LOI total 68.36 12.83 4.01 0.47 0.68 0.27 0.10 0.30 12.86 99.88

[0074] Example 1

[0075] This embodiment provides a method for preparing silica aerogel microspheres, comprising the following steps:

[0076] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 700°C for 1.5 h in an air atmosphere. It was then mixed with a 4 mol / L sodium hydroxide solution at a mass ratio of 1:7, subjected to alkaline dissolution treatment at 80°C for 4 h, and filtered to obtain a sodium silicate solution.

[0077] (2) Sodium silicate solution, isopropanol and water were mixed in a mass ratio of 1:8:2 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution was adjusted to 2 with a 4 mol / L hydrochloric acid solution, and the solution was hydrolyzed at 60° C. for 18 h to obtain a silica alcohol sol.

[0078] (3) Under constant stirring, the silica alcohol sol and 25% ammonia water by mass fraction were respectively injected into 50 mL of the oil phase by a peristaltic pump at a flow ratio of 1:4 until the pH of the oil phase mixture was 7. The oil phase contained paraffin oil, n-hexane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 5% based on the total volume of the oil phase as 100%, and the volume ratio of paraffin oil to n-hexane was 1:1. The mixture was then stirred for 15 minutes, and the silica wet gel microspheres were obtained by centrifugal separation.

[0079] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 18 hours at a surface modification temperature of 35° C. to obtain surface modified gel microspheres.

[0080] (5) The surface modified gel microspheres were first washed with methanol for 0.25 h and then dried in a vacuum oven at 60° C. for 12 h to obtain silica aerogel microspheres.

[0081] Example 2

[0082] This embodiment provides a method for preparing silica aerogel microspheres, comprising the following steps:

[0083] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 850°C for 1 h in an air atmosphere. It was then mixed with a 6 mol / L sodium hydroxide solution at a mass ratio of 1:5, subjected to alkaline dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0084] (2) Sodium silicate solution, ethylene glycol and water were mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution was adjusted to 1 with a 6 mol / L nitric acid solution, and the solution was hydrolyzed at 80° C. for 10 h to obtain a silicon dioxide alcohol sol.

[0085] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:3 through a peristaltic pump until the pH of the oil phase mixture reached 7. The oil phase contained diesel, n-heptane and TX-7 emulsifier. The volume of TX-7 emulsifier accounted for 2% of the total volume of the oil phase, and the volume ratio of diesel to n-heptane was 1.5:1. The mixture was then stirred for 20 minutes and centrifuged to obtain wet silica gel microspheres.

[0086] (4) The wet silica gel microspheres were placed in vinyl tri(β-methoxyethoxy) silane for surface modification for 12 hours at a temperature of 60°C to obtain surface modified gel microspheres.

[0087] (5) The surface modified gel microspheres were first washed with anhydrous ethanol for 0.25 h and then dried in a vacuum oven at 60° C. for 12 h to obtain silica aerogel microspheres.

[0088] Example 3

[0089] This embodiment provides a method for preparing silica aerogel microspheres, comprising the following steps:

[0090] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0091] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0092] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0093] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0094] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0095] Example 4

[0096] This embodiment provides a method for preparing silica aerogel microspheres, comprising the following steps:

[0097] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 800°C for 1.5 h in an air atmosphere. It was then mixed with a 5 mol / L sodium carbonate solution at a mass ratio of 1:8, subjected to alkali dissolution treatment at 80°C for 4 h, and filtered to obtain a sodium silicate solution.

[0098] (2) Sodium silicate solution, ethylene glycol and water were mixed in a mass ratio of 1:5:5 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution was adjusted to 2 with a 4 mol / L hydrochloric acid solution, and the solution was hydrolyzed at 60° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0099] (3) Under constant stirring, the silica alcohol sol and 25% ammonia water by mass fraction were respectively injected into 50 mL of the oil phase by a peristaltic pump at a flow ratio of 1:6 until the pH of the oil phase mixture reached 8. The oil phase contained paraffin oil, n-octane and TX-7 emulsifier. The volume proportion of TX-7 emulsifier was 6% based on the total volume of the oil phase as 100%, and the volume ratio of paraffin oil to n-octane was 1:1. The mixture was then stirred for 25 minutes and the silica wet gel microspheres were obtained by centrifugation.

[0100] (4) The wet silica gel microspheres were placed in vinyl tri(β-methoxyethoxy) silane for surface modification for 6 hours at a surface modification temperature of 30° C. to obtain surface modified gel microspheres.

[0101] (5) The surface modified gel microspheres were first washed with ethanol for 0.35 h and then dried in a vacuum oven at 70° C. for 10 h to obtain silica aerogel microspheres.

[0102] Example 5

[0103] The difference from Example 3 is that Example 5 adjusts the ratio of components in the oil phase so that the volume ratio of kerosene to n-heptane is 1.2:1. The specific preparation method comprises the following steps:

[0104] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0105] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0106] (3) Under continuous stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.2:1. The mixture was then stirred for 30 minutes and centrifuged to obtain the silica wet gel microspheres.

[0107] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0108] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0109] Example 6

[0110] The difference from Example 3 is that Example 6 adjusts the component ratio in the oil phase so that the volume ratio of kerosene to n-heptane is 1.4:1. The specific preparation method comprises the following steps:

[0111] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0112] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0113] (3) Under continuous stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.4:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0114] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0115] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0116] Example 7

[0117] The difference from Example 3 is that in Example 7, the mass ratio of sodium silicate solution, isopropanol and water in step (2) is adjusted to 1:10:4. The specific preparation method comprises the following steps:

[0118] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0119] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:10:4 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0120] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0121] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0122] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0123] Example 8

[0124] The difference from Example 3 is that in Example 8, kerosene is not added to the oil phase in step (3). The specific preparation method comprises the following steps:

[0125] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0126] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0127] (3) While stirring continuously, the silica alcohol sol and 28% ammonia water by mass were respectively injected into 50 mL of the oil phase by a peristaltic pump at a flow ratio of 1:5 until the pH of the oil phase mixture reached 8. The oil phase contained n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0128] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0129] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0130] Example 9

[0131] The difference from Example 3 is that in Example 9, n-heptane is not added to the oil phase in step (3). The specific preparation method comprises the following steps:

[0132] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0133] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0134] (3) While stirring continuously, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%. The mixture was then stirred for 30 minutes and centrifuged to obtain the silica wet gel microspheres.

[0135] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0136] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0137] Example 10

[0138] The difference from Example 3 is that in Example 10, the component ratio in the oil phase is adjusted in step (3) so that the volume ratio of kerosene to n-heptane is 1:2. The specific preparation method comprises the following steps:

[0139] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0140] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0141] (3) Under continuous stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1:2. The mixture was then stirred for 30 minutes and centrifuged to obtain the silica wet gel microspheres.

[0142] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0143] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0144] Embodiment 11

[0145] The difference from Example 3 is that in Example 11, the component ratio in the oil phase is adjusted in step (3) so that the volume ratio of kerosene to n-heptane is 2:1. The specific preparation method comprises the following steps:

[0146] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0147] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0148] (3) Under continuous stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 2:1. The mixture was then stirred for 30 minutes and centrifuged to obtain the silica wet gel microspheres.

[0149] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0150] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0151] Example 12

[0152] The difference from Example 3 is that in Example 12, the surface modification time in step (4) is adjusted to 2 hours, and the surface modification temperature is adjusted to 75° C. The specific preparation method comprises the following steps:

[0153] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0154] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0155] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0156] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 2 hours at a surface modification temperature of 75°C to obtain surface modified gel microspheres.

[0157] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0158] Example 13

[0159] The difference from Example 3 is that in Example 13, the surface modification time in step (4) is adjusted to 24 hours, and the surface modification temperature is adjusted to 15° C. The specific preparation method comprises the following steps:

[0160] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0161] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0162] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0163] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 24 hours at a surface modification temperature of 15°C to obtain surface modified gel microspheres.

[0164] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0165] Embodiment 14

[0166] The difference from Example 3 is that Example 14 adjusts the flow ratio of the silica alcohol sol and the ammonia water with a mass fraction of 28% to 1:1, and makes the pH of the oil phase mixed liquid = 7. The specific preparation method comprises the following steps:

[0167] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0168] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0169] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:1 through a peristaltic pump until the pH of the oil phase mixture reached 7. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0170] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0171] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0172] Embodiment 15

[0173] The difference from Example 3 is that in Example 15, the flow ratio of the silica alcohol sol and the ammonia water with a mass fraction of 28% is adjusted to 1:8, and the pH of the oil phase mixed liquid is set to 10. The specific preparation method comprises the following steps:

[0174] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0175] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0176] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:8 through a peristaltic pump until the pH of the oil phase mixture reached 10. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0177] (4) The wet silica gel microspheres were placed in vinyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0178] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0179] Comparative Example 1

[0180] The difference from Example 3 is that in step (4) of Comparative Example 1, the silica gel microspheres are placed in trimethylchlorosilane. The specific preparation method comprises the following steps:

[0181] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0182] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0183] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0184] (4) The silica wet gel microspheres were placed in trimethylchlorosilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0185] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0186] Comparative Example 2

[0187] The difference from Example 3 is that in step (4) of Comparative Example 2, the silica gel microspheres are placed in methyltrimethoxysilane. The specific preparation method comprises the following steps:

[0188] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0189] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0190] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0191] (4) The wet silica gel microspheres were placed in methyltrimethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0192] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0193] Comparative Example 3

[0194] The difference from Example 3 is that in step (4) of Comparative Example 3, the silica gel microspheres are placed in hexamethyldisilazane. The specific preparation method comprises the following steps:

[0195] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0196] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0197] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0198] (4) The silica wet gel microspheres were placed in hexamethyldisilazane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0199] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0200] Comparative Example 4

[0201] The difference from Example 3 is that in step (4) of Comparative Example 4, the silica gel microspheres are placed in trimethylethoxysilane. The specific preparation method comprises the following steps:

[0202] (1) The fly ash acid slag was placed in a muffle furnace and calcined at 600°C for 2 h in an air atmosphere. It was then mixed with a 4 mol / L sodium carbonate solution at a mass ratio of 1:5, subjected to an alkali dissolution treatment at 100°C for 2.5 h, and filtered to obtain a sodium silicate solution.

[0203] (2) Sodium silicate solution, isopropanol and water are mixed in a mass ratio of 1:7:3 to obtain a sodium silicate alcohol solution, the pH of the sodium silicate alcohol solution is adjusted to 3 using a 70% by mass ethanolic acid solution, and the solution is hydrolyzed at 70° C. for 18 h to obtain a silicon dioxide alcohol sol.

[0204] (3) Under constant stirring, the silica alcohol sol and 28% ammonia water by mass were injected into 50 mL of the oil phase at a flow ratio of 1:5 through a peristaltic pump until the pH of the oil phase mixture reached 8. The oil phase contained kerosene, n-heptane and OP-7 emulsifier, and the volume proportion of OP-7 emulsifier was 8% based on the total volume of the oil phase as 100%, and the volume ratio of kerosene to n-heptane was 1.5:1. The mixture was then stirred for 30 minutes, and the silica wet gel microspheres were obtained by centrifugation.

[0205] (4) The wet silica gel microspheres were placed in trimethylethoxysilane for surface modification for 12 hours at a surface modification temperature of 45°C to obtain surface modified gel microspheres.

[0206] (5) The surface modified gel microspheres were first washed with methanol for 0.5 h and then dried in a vacuum oven at 80 °C for 8 h to obtain silica aerogel microspheres.

[0207] Test Example 1

[0208] The contact angle, specific surface area, particle size distribution, and average pore size of the silica aerogel microspheres provided in the test examples and comparative examples are shown in Table 2.

[0209] Contact angle test method: JC2000D1 contact angle tester is used for testing, and the test temperature is 25℃.

[0210] Specific surface area test method: BET method was used to test in V-Sorb2800TP specific surface area analyzer.

[0211] Particle size distribution: SALD-3101 laser diffraction particle size distribution measuring instrument is used, and the laser wavelength is 690nm.

[0212] Average pore size: The BJH method was used to test the surface area of ​​the samples in a V-Sorb2800TP surface area analyzer.

[0213] Table 2

[0214]

[0215]

[0216] According to Examples 1-7 and Comparative Examples 1-4, by using vinyltrimethoxysilane and / or vinyltri(β-methoxyethoxy)silane to modify the surface of silica gel microspheres, the obtained silica aerogel has greater hydrophobicity and specific surface area, and smaller average pore size and particle size.

[0217] According to Examples 1-7 and 8-11, the oil phase includes three components: mineral oil, alkane and emulsifier. The total volume of the oil phase is 100%, the volume of the emulsifier accounts for 2-8%, and the volume ratio of mineral oil to alkane is (1-1.5):1. The silica aerogel microspheres prepared have high hydrophobicity and specific surface area, as well as small average pore size and particle size. It is shown that the oil phase in the present application effectively avoids the agglomeration of the silica wet gel microspheres, thereby improving the hydrophobicity and specific surface area of ​​the silica aerogel microspheres, and the oil phase is stable, avoiding the fragmentation of the silica wet gel microspheres during stirring.

[0218] According to Examples 1-7 and Examples 12-13, when the surface modification temperature is 30-60°C and the surface modification time is 6-18h, the prepared silica aerogel microspheres have higher hydrophobicity and specific surface area, and smaller average pore size and particle size.

[0219] According to Examples 1-7 and 14-15, when the flow ratio of silica alcohol sol to ammonia water is 1:3 to 1:6, it is more conducive to the production of silica aerogel microspheres with higher hydrophobicity and specific surface area, and smaller average pore size and particle size.

[0220] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0221] The silica aerogel microspheres obtained by the preparation method provided in the present application not only have high hydrophobicity and specific surface area, small average pore size and particle size, but also efficiently utilize fly ash acid slag to reduce costs. In addition, the preparation method is simple, easy to operate, and suitable for large-scale production.

[0222] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing silica aerogel microspheres, characterized in that: The steps include: Step S1, calcining, alkali dissolving and solid-liquid separation of fly ash acid slag in sequence to obtain a sodium silicate solution; Step S2, mixing the sodium silicate solution, alcohol and optionally water to obtain a sodium silicate alcohol solution, and hydrolyzing the sodium silicate alcohol solution to obtain a silicon dioxide alcohol sol; Step S3, respectively introducing the silica alcohol sol and ammonia water into the oil phase until the pH of the obtained oil phase mixed solution is 7-8, and performing solid-liquid separation to obtain silica wet gel microspheres; Step S4, using an organic siloxane compound to perform surface modification on the silicon dioxide wet gel microspheres to obtain surface modified gel microspheres; Wherein, the organosiloxane compound includes at least one of vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane; Step S5, washing and drying the surface modified gel microspheres to obtain silica aerogel microspheres.

2. The preparation method according to claim 1, characterized in that: In the step S1, the fly ash acid slag mainly includes SiO2 and Al2O3, wherein the mass fraction of SiO2 is 60-70wt%, and the mass fraction of Al2O3 is 10-25wt%.

3. The preparation method according to claim 1, characterized in that: In the step S1, the calcination temperature is 600-850° C., and the calcination time is 1-2 hours.

4. The preparation method according to claim 1, characterized in that: In the step S1, the alkaline solution is used for the alkaline dissolution treatment, and the alkaline solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, and a sodium carbonate solution; Preferably, the concentration of the alkaline solution is 4 to 6 mol / L; Preferably, the mass ratio of the fly ash acid slag to the alkaline solution is 1:5 to 1:9; Preferably, the temperature of the alkali dissolution treatment is 60-100° C.; the time of the alkali dissolution treatment is 2.5-5 h.

5. The preparation method according to claim 1, characterized in that: In the step S2, the mass ratio of the sodium silicate solution, the alcohol and the optional water is 1:(5-10):(2-5); And / or, the alcohol comprises at least one of isopropanol and ethylene glycol; And / or, the temperature of the hydrolysis treatment is 40 to 80° C., and the time of the hydrolysis treatment is 6 to 24 hours.

6. The preparation method according to claim 1, characterized in that: In the step S2, an acid solution is used to adjust the pH of the sodium silicate alcohol solution to 1-3 before the hydrolysis treatment is performed; And / or, the acid solution includes at least one of an inorganic acid solution and an organic acid solution; Preferably, the inorganic acid solution includes at least one of a hydrochloric acid solution and a nitric acid solution; Preferably, the organic acid solution is a glycolic acid solution; Preferably, the concentration of the inorganic acid solution is 4-6 mol / L.

7. The preparation method according to claim 1, characterized in that: In step S3, the oil phase includes mineral oil, alkane and emulsifier; wherein, based on the total volume of the oil phase being 100%, the volume proportion of the emulsifier is 2-8%, and the volume ratio of mineral oil to alkane is (1-1.5):1; Preferably, the mineral oil includes at least one of paraffin oil, diesel and kerosene; Preferably, the alkane includes at least one of n-heptane, n-hexane and n-octane; Preferably, the emulsifier includes at least one of OP-7 and TX-7.

8. The preparation method according to claim 1, characterized in that: In the step S3, the flow ratio of the silica alcohol sol to the ammonia water is 1:3 to 1:6; preferably, the mass fraction of the ammonia water is 25 to 28%.

9. The preparation method according to claim 1, characterized in that: The surface modification temperature is 30-60° C., and the surface modification time is 6-18 hours.

10. The preparation method according to claim 1, characterized in that: In the step S5, the washing is performed using a washing solution, wherein the washing solution includes at least one of methanol and anhydrous ethanol; And / or, the washing time is 0.25-0.5h; And / or, the drying temperature is 50-80° C., and the drying time is 8-16 hours.

Citation Information

Cited By

  • Method for preparing thermal insulation coating from coal gasification slag

    CN121160124A